Faktor – Faktor Yang Mempengaruhi Keahlian Komputer Akuntansi Pada Mahasiswa Jurusan Akuntansi Perguruan Tinggi Swasta Di Kota Medan - Rima Novita Sari; Widia Astuty; Irfan (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The purposes of this study are to examine and analyze factors that effect on accounting computer skills which are accounting laboratory facilities, computer attitudes, computer anxiety and computer knowledge. The population in this study are students in accounting major at private universities in Medan. Based on purposive random sampling method, there were 18 private universities that have accounting major. The data analysis technique used that Partial Least Square (PLS) approach. PLS is a component or variant based Structural Equation Model (SEM). The results showed that laboratory facilities, computer attitudes, and computer knowledge had a positive effect on accounting computer skills, while computer anxiety had a negative effect.